Terbium-doped NASICON type sodium ion conductor material and preparation method thereof
By doping terbium into Na3Zr2Si2PO12, Na3+xZr2-xTbxSi2PO12 type sodium ion conductor material was prepared, which solved the problems of flammability and insufficient conductivity of liquid electrolytes in sodium ion batteries, and achieved high ionic conductivity and stability improvement. Reduces sintering temperature and energy consumption.
Patent Information
- Application Number
- CN202411388818.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-08
AI Technical Summary
The liquid electrolytes used in existing sodium ion batteries are flammable, with risks of electrolyte leakage and thermal runaway, and the ionic conductivity of NASICON type solid electrolytes has not yet met the requirements for commercial applications.
By doping terbium with different contents into Na3Zr2Si2PO12, a terbium-doped NASICON type sodium ion conductor material of Na3+xZr2-xTbxSi2PO12 type was prepared to improve its ionic conductivity and enhance the ability to inhibit sodium dendrites' growth.
The high ionic conductivity is improved, the interface performance is improved, the grain size is reduced, the dendrites are suppressed, the size and conductivity of sodium ion transport channels are improved, the sintering temperature is reduced, and energy consumption is reduced. Enhanced battery safety and stability.
Smart Images

Figure CN119241231A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of sodium ion solid electrolyte manufacturing, and specifically relates to a terbium-doped NASICON type sodium ion conductor material and a preparation method thereof. Background Art
[0002] Electrochemical energy storage technology, as an important bridge connecting energy production and consumption, is gradually becoming a key force in promoting global energy transformation. Faced with the increasing depletion of traditional fossil energy and increasingly severe environmental pollution problems, electrochemical energy storage has shown great application potential and development prospects with its advantages such as high energy density, rapid response and flexible configuration. Electrochemical energy storage systems mainly include various types of batteries and supercapacitors, which realize the mutual conversion and storage of electrical energy and chemical energy through electrochemical reactions. With the continuous advancement of science and technology, these systems have significantly improved in energy conversion efficiency, cycle stability and cost-effectiveness.
[0003] Among various commercial rechargeable chemical energy storage devices, sodium-ion batteries have the advantages of abundant resources and low cost, high safety, strong environmental adaptability, and good power characteristics, and are often used in pocket electronic devices. Currently, commercial sodium-ion batteries generally use a liquid electrolyte system. Although this system has high ionic conductivity, it faces safety risks caused by electrolyte leakage and potential redox reactions in actual application. The carbonate electrolytes currently used in sodium-ion batteries are highly flammable, which makes the battery at risk of fire or even explosion under thermal runaway conditions, making it difficult to use in electric vehicles and large-scale renewable energy storage (such as solar and wind energy).
[0004] In order to improve safety and durability, in addition to simplifying battery design, replacing flammable liquid electrolytes with solid electrolytes has also received increasing attention. Solid electrolytes have better safety and stable chemical properties, which are conducive to long-term recycling and further improve their energy density. In 1976, Goodenough and Hong et al. proposed the NASICON material Na 1+x Zr2Si x P 3-x O 12 The synthesis and properties of (0≤x≤3), especially when x=2, Na3Zr2Si2PO 12 It has the highest ionic conductivity at room temperature (10 -4 S / cm). This groundbreaking research laid the foundation for the subsequent application of NASICON-type materials in the field of solid-state battery electrolytes. The study found that: Na3Zr2Si2PO 12It has the advantages of being environmentally friendly, excellent chemical and electrochemical stability, and relatively high ionic conductivity. 12 Solid electrolytes exhibit many advantages in electrochemical properties, but in terms of commercial production and application, their ionic conductivity still has room for improvement compared with the leading technologies currently on the market (Y. Bhaskara Rao, K. Ramakrushna Achary, et al. Journal of Materials Science, 58: 2222-2233, 2023).
[0005] Na3Zr2Si2PO 12 Solid electrolytes have two structures: rhombohedral and monoclinic. Monoclinic NASICON has lower ionic conductivity but generally has better chemical stability, while rhombohedral NASICON is more symmetrical than the distorted monoclinic phase and thus has higher ionic conductivity, but this phase is not as chemically stable as the monoclinic phase (Park, Nezafati, et al. ACS Appl, 8:27814-27824, 2016).
[0006] Therefore, how to improve the chemical stability of the rhombohedral phase is the key to improving the ionic conductivity of NASICON-type solid electrolyte ceramics. Summary of the invention
[0007] The first object of the present invention is to provide a terbium-doped NASICON type sodium ion conductor material in view of the problems existing in the technical background. The present invention is to dope different contents of terbium into Na3Zr2Si2PO 12 In solid electrolytes, high ionic conductivity is achieved while enhancing the ability of NASICON materials to inhibit the growth of sodium dendrites.
[0008] Another object of the present invention is to provide a method for preparing a terbium-doped NASICON type sodium ion conductor material.
[0009] The technical solution adopted to achieve the first object of the present invention is: a terbium-doped NASICON type sodium ion conductor material, whose stoichiometric formula is Na 3+x Zr 2-x Tb x Si2PO 12 , where 0<x≤0.3.
[0010] Preferably, the total ionic conductivity of the terbium-doped NASICON type sodium ion conductor material of the present invention is 3.07×10 -4 S / cm~1.02×10 -3 S / cm.
[0011] The technical solution used to achieve another purpose of the present invention is: a method for preparing a terbium-doped NASICON type sodium ion conductor material, which is carried out according to the following steps: 1) Processing of raw material powders: calcining Na2CO3 powder and ZrO2 powder at high temperature, and drying SiO2 powder, NH4H2PO4 powder and Tb2O3 powder; 2) Weighing and batching: Based on Na 3+x Zr 2-x Tb x Si2PO 12 Weigh the Na2CO3, ZrO2, SiO2, NH4H2PO4 and Tb2O3 raw material powders processed in step 1) according to the stoichiometric ratio of Na, Zr, Tb, Si and P, wherein excess Na2CO3 and NH4H2PO4 are weighed to compensate for the volatilization loss of sodium at high temperature; 3) Grinding and mixing: In a dust-free environment, ball-mill the weighed raw material powder and grinding aid to mix them evenly; evenly load the ball-milled mixed powder into the crucible and ensure that the crucible cover is sealed; 4) Powder synthesis: Place the crucible loaded with the mixed powder in step 3) into a preheated muffle furnace, heat it to 900-1000°C at a rate of 3-5°C / min, and maintain it in this temperature range for 6-12 hours, let the crucible cool naturally to 180-220°C with the furnace temperature, take out the synthesized powder, and grind it in a mortar to obtain the final precursor powder; 5) Granulation and tableting: weigh the precursor powder obtained in step 4) above, add polyvinyl butyral solution to the precursor powder, grind in an agate mortar to mix the powder and polyvinyl alcohol solution evenly, and after completely drying, put the powder into a mold for granulation, and keep the granulated powder under pressure to obtain a solid electrolyte formed sheet; 6) Debinding: Place the solid electrolyte formed sheet pressed in step 5) in an oven, preheat, take out the solid electrolyte formed sheet and cool it to room temperature, then place it upright in an open crucible in a muffle furnace for debinding. After debinding, turn off the heating and allow the solid electrolyte formed sheet to cool naturally to room temperature along with the temperature in the furnace to obtain a sample sheet; 7) Sintering: Before sintering, use the mother powder of the same composition to spread on the inner side of the alumina crucible, compact the mother powder to ensure that it is evenly distributed on the surface of the crucible cover, place the sample sheet obtained in step 6) on the mother powder, and then cover it with the mother powder of the same composition. Finally, turn the crucible upside down on the alumina crucible cover and gently press the crucible and the crucible cover to ensure the sealing. Immediately put the sealed crucible into a muffle furnace and heat it to 900-1000°C at a heating rate of 5°C / min, then heat it to 1100-1200°C at a rate of 3°C / min, and then keep it at this temperature for 6-12h. After cooling, open the crucible cover and take out the dense crystalline ceramic material.
[0012] Preferably, in step 1) of the present invention, the high temperature calcination conditions of Na2CO3 powder are: calcination temperature 900°C, calcination time 5 to 9 hours; the high temperature calcination conditions of ZrO2 powder are: calcination temperature 900°C, calcination time 8 to 12 hours; the drying conditions of SiO2, NH4H2PO4 and Tb2O3 are: drying at 120°C for 12 to 24 hours.
[0013] Preferably, in step 3) of the present invention, the grinding aid is anhydrous ethanol, and the ball milling conditions are: ball milling at a rate of 1200 r / min for 0.5 to 1 hour.
[0014] Preferably, in step 5) of the present invention, the amount of the polyvinyl alcohol solution added is 20% of the precursor powder, and the mass concentration of the polyvinyl alcohol solution is 5%.
[0015] Preferably, in step 6) of the present invention, the method of debinding treatment is: firstly heating to 500°C at 1°C / min, and keeping at 500°C for 2 hours for debinding treatment.
[0016] Compared with the prior art, the technical advantages of the present invention are: The present invention first prepares Na3Zr2Si2PO 12 The sodium ion conductor material is then appropriately doped with terbium to increase its ionic conductivity, improve its interface performance, reduce interface impedance, reduce grain size, effectively inhibit dendrite growth, and demonstrate better interface compatibility.
[0017] The raw materials selected by the present invention are economical and practical oxides, which are not only easy to purchase but also low in price, thus helping to reduce production costs.
[0018] Thanks to the efficient conversion process, the preparation process of the present invention can improve the utilization efficiency of raw materials, and the terbium-doped NASICON-type sodium ion conductor material can effectively reduce its sintering temperature and reduce energy consumption.
[0019] The present invention replaces the framework ions (such as Zr 4+ ), increasing the concentration of mobile sodium ions, thereby improving ionic conductivity. The doping of terbium ions in the present invention effectively increases the size of the sodium ion transmission channel, reduces the transmission energy barrier, and thus improves ionic conductivity. 3.2 Zr 1.8 Tb 0.2 Si2PO 12 The ionic conductivity of the electrolyte at room temperature reached 1.02×10 -3 S / cm. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 Na synthesized in Examples 1-3 of the present invention 3+x Zr 2-x Tb x Si2PO 12 (0<x≤0.3) Ceramic samples and Na3Zr2Si2PO synthesized in Comparative Example 1 12 X-ray diffraction patterns of ceramic samples.
[0021] Figure 2 The Na synthesized in Example 2 of the present invention 3.2 Zr 1.8 Tb 0.2 Si2PO 12 Microstructure of ceramic samples.
[0022] Figure 3 Na synthesized in Examples 1-3 of the present invention 3+x Zr 2-x Tb x Si2PO 12 (0<x≤0.3) Ceramic samples and Na3Zr2Si2PO synthesized in Comparative Example 1 12 AC impedance spectroscopy of ceramic samples.
[0023] Figure 4 Na synthesized in Examples 1-3 of the present invention 3+x Z r2-x Tb x Si2PO 12 (0<x≤0.3) Ceramic samples and Na3Zr2Si2PO synthesized in Comparative Example 1 12 Polarization current-time curves of the electrolyte of the ceramic sample when an external voltage of 1 V is applied for (a) 2000 s, (b) 500 s.
[0024] Figure 5 Na synthesized in Examples 1-3 of the present invention 3+x Z r2-xTb x Si2PO 12 (0<x≤0.3) Ceramic samples and Na3Zr2Si2PO synthesized in Comparative Example 1 12 (b) Polarization current-time curve of the electrolyte of the ceramic sample when an external voltage of 1 V is applied for 500 s. DETAILED DESCRIPTION
[0025] The present invention is further described below with reference to Examples and Comparative Examples. Example 1
[0026] (1) Na 3.1 Zr 1.9 Tb 0.1 Si2PO 12 Treatment of raw material powders: Sodium carbonate (Na2CO3) was calcined at 900°C for 5 hours to promote its decomposition and purification, zirconium oxide (ZrO2) was calcined at 900°C for 8 hours to remove adsorbed moisture and possible organic matter, and silicon dioxide (SiO2), ammonium hydrogen phosphate (NH4H2PO4) and terbium oxide (Tb2O3) were dried at 120°C for 15 hours; (2) Weighing and mixing: According to the synthesis of 7g Na 3.1 Zr 1.9 Tb 0.1 Si2PO 12 The raw material powders after weighing the stoichiometric ratio of Na, Zr, Tb, Si, and P are as follows: (Na2CO399%) 2.1312g, (ZrO299%) 3.0623g, (SiO299%) 1.5587g, (NH4H2PO499%) 1.4659g, (Tb2O399%) 0.2372g, wherein 15wt% excess Na2CO3 and NH4H2PO4 are weighed to compensate for the volatilization loss of sodium at high temperature; (3) Grinding and mixing: In a dust-free environment, place the weighed raw material powder in a clean agate mortar, add anhydrous ethanol as a grinding aid, and ball-mill at a rate of 1200 r / min for 0.5 h. Grind and mix evenly, and evenly load the ball-milled mixture into a crucible, and ensure that the crucible lid is sealed to prevent volatilization and oxidation; (4) Powder synthesis: The crucible loaded with the ball-milled mixture was steadily placed in a preheated muffle furnace, and the temperature was raised to 950°C at a rate of 4°C / min and maintained at this temperature for 6 hours. The crucible was allowed to cool naturally to about 200°C along with the furnace temperature. After taking out the synthesized powder, it was ground in a mortar for 30 minutes to improve its fineness and uniformity, so as to obtain the final precursor powder. (5) Granulation and tableting: Weigh 0.7 g of the precursor powder obtained in step (4) above, add a 5% polyvinyl butyral (PVB) solution to the precursor powder to enhance the adhesion of the powder. The amount of PVB solution added is 20% of the mass of the precursor powder. Grind the precursor powder and the PVB solution in an agate mortar to mix them evenly. After they are completely dried, place the powder in a mold and keep it under a pressure of 30 MPa for 1 min before granulation. Keep the granulated powder under a pressure of 50 MPa for 1 min to obtain a solid electrolyte formed sheet with a diameter of 10 mm and a thickness of 1.7 mm. (6) Debinding: Place the solid electrolyte formed sheet pressed in step (5) in an oven at 50°C to remove the anhydrous ethanol in the binder. After preheating, take out the formed sheet and cool it to room temperature. Then, place it upright in an open crucible in a muffle furnace and heat it to 500°C at a rate of 1°C / min. Keep it at 500°C for 2 hours to perform debinding treatment to ensure complete volatilization of organic matter. After debinding is completed, turn off the heating and let the formed sheet cool naturally to room temperature along with the temperature in the furnace to obtain a sample sheet. (7) Sintering: Before sintering, use mother powder of the same composition to spread about 1 mm thick on the inside of the alumina crucible, gently compact the mother powder, place the sample sheet obtained in step (6) on the above mother powder, and then cover it with mother powder of the same composition. Finally, invert the crucible on the alumina crucible cover and gently press the crucible and crucible cover to ensure the sealing. Immediately put the sealed crucible into a muffle furnace and heat it to 950°C at a rate of 5°C / min, then heat it to 1150°C at a rate of 3°C / min, and then keep it at this temperature for 8 h. After cooling, open the crucible cover and take out the dense crystalline ceramic material. Example 2
[0027] (1) Na 3.2 Zr 1.8 Tb 0.2 Si2PO 12 Treatment of raw powders: Sodium carbonate (Na2CO3) is calcined at 900°C for 7 hours to promote its decomposition and purification, zirconium oxide (ZrO2) is calcined at 900°C for 10 hours to remove adsorbed moisture and possible organic matter, and silicon dioxide (SiO2), ammonium hydrogen phosphate (NH4H2PO4) and terbium oxide (Tb2O3) are dried at 120°C for 18 hours; (2) Weighing and mixing: Synthesize 9g Na 3.2 Zr 1.8 Tb 0.2 Si2PO 12The stoichiometric weighing step (1) of Na, Zr, Tb, Si and P requires 2.7533 g (Na2CO399%), 3.6010 g (ZrO299%), 1.9512 g (SiO299%), 1.8351 g (NH4H2PO499%) and 0.5940 g (Tb2O399%) of raw material powders, wherein 15 wt% excess Na2CO3 and NH4H2PO4 are weighed to compensate for the volatilization loss of sodium at high temperature; (3) Grinding and mixing: In a dust-free environment, place the weighed raw material powder in a clean agate mortar, add anhydrous ethanol as a grinding aid, and ball mill at a rate of 1200r / min for 1 hour to grind and mix evenly. Load the ball-milled mixture evenly into the crucible and ensure that the crucible lid is sealed to prevent volatilization and oxidation; (4) Powder synthesis: Place the crucible loaded with raw materials steadily into a preheated muffle furnace, heat it to 980°C at a rate of 4°C / min, and keep it in this temperature range for 6 hours. Allow the crucible to cool naturally to about 200°C along with the furnace temperature. After taking out the synthesized powder, grind it in a mortar for 60 minutes to improve its fineness and uniformity to obtain the final powder; (5) Granulation and tableting: Weigh 0.8 g of the precursor powder obtained in step (4) above, and add a 5% mass concentration of polyvinyl butyral (PVB) solution to the powder to enhance the adhesion of the powder. The amount of PVB solution added is 20% of the mass of the precursor powder. Grind in an agate mortar to mix the powder and the PVB solution evenly. After it is completely dried, place the powder in a mold and keep it under a pressure of 30 MPa for 1 min for granulation. Keep the granulated powder under a pressure of 50 MPa for 1 min to obtain a solid electrolyte formed sheet with a diameter of 10 mm and a thickness of 2.0 mm; (6) Debinding: Place the molded sheet pressed in step (5) in an oven at 50°C to remove the anhydrous ethanol in the adhesive. After preheating, take out the molded sheet and cool it to room temperature, then place it upright in an open crucible in a muffle furnace, heat it to 500°C at a rate of 1°C / min, and keep it at 500°C for 2 hours to perform debinding treatment to ensure complete volatilization of organic matter. After debinding is completed, turn off the heating and let the molded sheet cool naturally to room temperature along with the temperature in the furnace to obtain a sample sheet; (7) Sintering: Before sintering, use mother powder of the same composition to spread about 1 mm thick on the inside of the alumina crucible. Use a tool to gently compact the mother powder. Place the sample obtained in step (6) on the above mother powder, and then cover it with mother powder of the same composition. Finally, invert the crucible on the alumina crucible lid and gently press the crucible and crucible lid to ensure sealing. Immediately put the sealed crucible into a muffle furnace and heat it to 1000°C at a heating rate of 5°C / min, then heat it to 1180°C at a rate of 3°C / min, and then keep it at this temperature for 10 h. After cooling, open the crucible lid and take out the dense crystalline ceramic material. Example 3
[0028] (1) Na 3.3 Zr 1.9 Tb 0.3 Si2PO 12 Treatment of raw powders: Sodium carbonate (Na2CO3) was calcined at 900°C for 9 hours to promote its decomposition and purification, zirconium oxide (ZrO2) was calcined at 900°C for 12 hours to remove adsorbed moisture and possible organic matter, and silicon dioxide (SiO2), ammonium hydrogen phosphate (NH4H2PO4) and terbium oxide (Tb2O3) were dried at 120°C for 24 hours; (2) Weighing and mixing: Synthesize 12 g Na 3.3 Zr 1.9 Tb 0.3 Si2PO 12 The stoichiometric weighing step (a) of Na, Zr, Tb, Si and P requires 3.7843 g (Na2CO3 99%), 5.0666 g (ZrO2 99%), 2.6009 g (SiO2 99%), 2.4461 g (NH4H2PO4 99%) and 1.1877 g (Tb2O3 99%) of raw material powders, wherein 15 wt% excess Na2CO3 and NH4H2PO4 are weighed to compensate for the volatilization loss of sodium at high temperature; (3) Grinding and mixing: In a dust-free environment, place the weighed raw material powder in a clean agate mortar, add anhydrous ethanol as a grinding aid, and ball mill at a rate of 1200r / min for 1 hour to grind and mix evenly. Load the ball-milled mixture evenly into the crucible and ensure that the crucible lid is sealed to prevent volatilization and oxidation; (4) Powder synthesis: Place the crucible loaded with raw materials steadily into a preheated muffle furnace, heat it to 1000°C at a rate of 5°C / min, and keep it in this temperature range for 6 hours. Allow the crucible to cool naturally to about 200°C along with the furnace temperature. After taking out the synthesized powder, grind it in a mortar for 60 minutes to improve its fineness and uniformity to obtain the final powder; (5) Granulation and tableting: Weigh 0.8 g of the precursor powder obtained in the above step (d), and add a 5% mass concentration of polyvinyl butyral (PVB) solution to the powder to enhance the adhesion of the powder. Grind in an agate mortar to mix the powder and PVB solution evenly. The amount of PVB solution added is 20% of the mass of the precursor powder. After it is completely dried, the powder is placed in a mold and kept at a pressure of 30 MPa for 1 minute for granulation. The granulated powder is kept at a pressure of 50 MPa for 1 minute to obtain a solid electrolyte formed sheet with a diameter of 10 mm and a thickness of 1.8 mm; (6) Debinding: Place the molded sheet pressed in step (5) in an oven at 50°C to remove the anhydrous ethanol in the adhesive. After preheating, take out the molded sheet and cool it to room temperature, then place it upright in an open crucible in a muffle furnace, heat it to 500°C at a rate of 1°C / min, and keep it at 500°C for 2 hours to perform debinding treatment to ensure complete volatilization of organic matter. After debinding is completed, turn off the heating and let the molded sheet cool naturally to room temperature along with the temperature in the furnace to obtain a sample sheet; (7) Sintering: Before sintering, use the mother powder of the same composition to spread about 1mm thick on the inside of the alumina crucible, and gently compact the mother powder. Place the sample sheet obtained in step (6) on the above mother powder, and then cover it with the mother powder of the same composition. Finally, invert the crucible on the alumina crucible cover and gently press the crucible and crucible cover to ensure sealing. Immediately put the sealed crucible into the muffle furnace and heat it to 1000℃ at a rate of 5℃ / min, then heat it to 1200℃ at a rate of 3℃ / min, and then keep it at this temperature for 12h. After cooling, open the crucible cover and take out the dense crystalline ceramic material. Example 4
[0029] (1) Na 3.15 Zr 1.85 Tb 0.15 Si2PO 12 Treatment of raw material powders: Sodium carbonate (Na2CO3) was calcined at 900°C for 9 hours to promote its decomposition and purification, zirconium oxide (ZrO2) was calcined at 900°C for 9 hours to remove adsorbed moisture and possible organic matter, and silicon dioxide (SiO2), ammonium hydrogen phosphate (NH4H2PO4) and terbium oxide (Tb2O3) were dried at 120°C for 18 hours; (2) Weighing and mixing: Synthesize 9g Na 3.15 Zr 1.85 Tb 0.15 Si2PO 12The stoichiometric weighing step (1) of Na, Zr, Tb, Si and P requires 2.7336 g (Na2CO3 99%), 3.7325 g (ZrO2 99%), 1.9678 g (SiO2 99%), 1.8825 g (NH4H2PO4 99%) and 0.4493 g (Tb2O3 99%) of raw material powders, wherein 15 wt% excess Na2CO3 and NH4H2PO4 are weighed to compensate for the volatilization loss of sodium at high temperature; (3) Grinding and mixing: In a dust-free environment, place the weighed raw material powder in a clean agate mortar, add anhydrous ethanol as a grinding aid, and ball mill at a rate of 1200r / min for 0.5 hours to grind and mix evenly. Load the ball-milled mixture evenly into the crucible and ensure that the crucible lid is sealed to prevent volatilization and oxidation; (4) Powder synthesis: The crucible loaded with raw materials is placed steadily in a preheated muffle furnace, and the temperature is raised to 1000°C at a rate of 4°C / min, and maintained in this temperature range for 6 hours, and the crucible is allowed to cool naturally to about 200°C along with the furnace temperature. After taking out the synthesized powder, it is ground in a mortar for 60 minutes to improve its fineness and uniformity to obtain the final powder; (5) Granulation and tableting: Weigh 0.7 g of the precursor powder obtained in step (4) above, add a 5% mass concentration of polyvinyl butyral (PVB) solution to the powder to enhance the adhesion of the powder. The amount of PVB solution added is 20% of the mass of the precursor powder. Grind in an agate mortar to mix the powder and PVB solution evenly. After it is completely dried, place the powder in a mold and keep it under a pressure of 30 MPa for 1 min for granulation. Keep the granulated powder under a pressure of 50 MPa for 1 min to obtain a solid electrolyte formed sheet with a diameter of 10 mm and a thickness of 1.8 mm; (6) Debinding: Place the molded sheet pressed in step (5) in an oven at 50°C to remove the anhydrous ethanol in the adhesive. After preheating, take out the molded sheet and cool it to room temperature, then place it upright in an open crucible in a muffle furnace, heat it to 500°C at a rate of 1°C / min, and keep it at 500°C for 2 hours to perform debinding treatment to ensure complete volatilization of organic matter. After debinding is completed, turn off the heating and let the molded sheet cool naturally to room temperature along with the temperature in the furnace to obtain a sample sheet; (7) Sintering: Before sintering, use the mother powder of the same composition to spread about 1mm thick on the inside of the alumina crucible, and use a tool to gently compact the mother powder. Place the sample sheet obtained in step (6) on the above mother powder, and then cover it with the mother powder of the same composition. Finally, invert the crucible on the alumina crucible lid and gently press the crucible and crucible lid to ensure sealing. Immediately put the sealed crucible into the muffle furnace and heat it to 1000℃ at a rate of 5℃ / min, then heat it to 1180℃ at a rate of 3℃ / min, and then keep it at this temperature for 12h. After cooling, open the crucible lid and take out the dense crystalline ceramic material. Example 5
[0030] (1) Na 3.05 Zr 1.95 Tb 0.05 Si2PO 12 Treatment of raw powders: Sodium carbonate (Na2CO3) was calcined at 900°C for 6 hours to promote its decomposition and purification, zirconium oxide (ZrO2) was calcined at 900°C for 12 hours to remove adsorbed moisture and possible organic matter, and silicon dioxide (SiO2), ammonium hydrogen phosphate (NH4H2PO4) and terbium oxide (Tb2O3) were dried at 120°C for 24 hours; (2) Weighing and mixing: Synthesize 12 g Na 3.05 Zr 1.95 Tb 0.05 Si2PO 12 The stoichiometric weighing step (1) of Na, Zr, Tb, Si and P requires 3.7064g (Na2CO3 99%), 5.3346g (ZrO2 99%), 2.6682g (SiO2 99%), 2.5525g (NH4H2PO4 99%) and 0.2031g (Tb2O3 99%) of raw material powders, wherein 15wt% excess Na2CO3 and NH4H2PO4 are weighed to compensate for the volatilization loss of sodium at high temperature; (3) Grinding and mixing: In a dust-free environment, place the weighed raw material powder in a clean agate mortar, add anhydrous ethanol as a grinding aid, and ball mill at a rate of 1200r / min for 1 hour to grind and mix evenly. Load the ball-milled mixture evenly into the crucible and ensure that the crucible lid is sealed to prevent volatilization and oxidation; (4) Powder synthesis: The crucible loaded with raw materials is placed steadily in a preheated muffle furnace, and the temperature is raised to 950°C at a rate of 5°C / min, and maintained in this temperature range for 6 hours, and the crucible is allowed to cool naturally to about 200°C along with the furnace temperature. After taking out the synthesized powder, it is ground in a mortar for 40 minutes to improve its fineness and uniformity to obtain the final powder; (5) Granulation and tableting: Weigh 0.8 g of the precursor powder obtained in step (4) above, add a 5% mass concentration of polyvinyl butyral (PVB) solution to the powder to enhance the adhesion of the powder. The amount of PVB solution added is 20% of the mass of the precursor powder. Grind in an agate mortar to mix the powder and PVB solution evenly. After it is completely dried, place the powder in a mold and keep it under a pressure of 30 MPa for 1 min for granulation. Keep the granulated powder under a pressure of 50 MPa for 1 min to obtain a solid electrolyte formed sheet with a diameter of 10 mm and a thickness of 2.0 mm; (6) Debinding: Place the molded sheet pressed in step (5) in an oven at 50°C to remove the anhydrous ethanol in the adhesive. After preheating, take out the molded sheet and cool it to room temperature, then place it upright in an open crucible in a muffle furnace, heat it to 500°C at a rate of 1°C / min, and keep it at 500°C for 2 hours to perform debinding treatment to ensure complete volatilization of organic matter. After debinding is completed, turn off the heating and let the molded sheet cool naturally to room temperature along with the temperature in the furnace to obtain a sample sheet; (7) Sintering: Before sintering, use the mother powder of the same composition to spread about 1mm thick on the inside of the alumina crucible, and use a tool to gently compact the mother powder. Place the sample sheet obtained in step (6) on the above mother powder, and then cover it with the mother powder of the same composition. Finally, invert the crucible on the alumina crucible cover and gently press the crucible and crucible cover to ensure sealing. Immediately put the sealed crucible into the muffle furnace and heat it to 950℃ at a rate of 5℃ / min, then heat it to 1150℃ at a rate of 3℃ / min, and then keep it at this temperature for 9h. After cooling, open the crucible cover and take out the dense crystalline ceramic material. Example 6
[0031] (1) Na 3.25 Zr 1.75 Tb 0.25 Si2PO 12 Treatment of raw material powders: Sodium carbonate (Na2CO3) is calcined at 900°C for 9 hours to promote its decomposition and purification, zirconium oxide (ZrO2) is calcined at 900°C for 12 hours to remove adsorbed moisture and possible organic matter, and silicon dioxide (SiO2), ammonium hydrogen phosphate (NH4H2PO4) and terbium oxide (Tb2O3) are dried at 120°C for 12 hours; (2) Weighing and mixing: Synthesize 5g Na 3.25 Zr 1.75 Tb 0.25 Si2PO 12The stoichiometric weighing step (1) of Na, Zr, Tb, Si and P requires 1.4936 g (Na2CO3 99%), 1.9292 g (ZrO2 99%), 1.0753 g (SiO2 99%), 1.0287 g (NH4H2PO4 99%) and 0.3913 g (Tb2O3 99%) of raw material powders, wherein 15 wt% excess Na2CO3 and NH4H2PO4 are weighed to compensate for the volatilization loss of sodium at high temperature; (3) Grinding and mixing: In a dust-free environment, place the weighed raw material powder in a clean agate mortar, add anhydrous ethanol as a grinding aid, and ball mill at a rate of 1200r / min for 1 hour to grind and mix evenly. Load the ball-milled mixture evenly into the crucible and ensure that the crucible lid is sealed to prevent volatilization and oxidation; (4) Powder synthesis: The crucible loaded with raw materials is placed steadily in a preheated muffle furnace, and the temperature is raised to 900°C at a rate of 4°C / min, and maintained in this temperature range for 6 hours, and the crucible is allowed to cool naturally to about 200°C along with the furnace temperature. After taking out the synthesized powder, it is ground in a mortar for 50 minutes to improve its fineness and uniformity to obtain the final powder; (5) Granulation and tableting: Weigh 0.7 g of the precursor powder obtained in step (4) above, add 5% by weight of polyvinyl butyral (PVB) solution to the powder to enhance the adhesion of the powder. The amount of PVB solution added is 20% of the mass of the precursor powder. Grind in an agate mortar to mix the powder and PVB solution evenly. After it is completely dried, place the powder in a mold and keep it under a pressure of 30 MPa for 1 min for granulation. Keep the granulated powder under a pressure of 50 MPa for 1 min to obtain a solid electrolyte formed sheet with a diameter of 10 mm and a thickness of 1.8 mm; (6) Debinding: Place the molded sheet pressed in step (5) in an oven at 50°C to remove the anhydrous ethanol in the adhesive. After preheating, take out the molded sheet and cool it to room temperature, then place it upright in an open crucible in a muffle furnace, heat it to 500°C at a rate of 1°C / min, and keep it at 500°C for 2 hours to perform debinding treatment to ensure complete volatilization of organic matter. After debinding is completed, turn off the heating and let the molded sheet cool naturally to room temperature along with the temperature in the furnace to obtain a sample sheet; (7) Sintering: Before sintering, use the mother powder of the same composition to spread about 1mm thick on the inside of the alumina crucible, and use a tool to gently compact the mother powder. Place the sample sheet obtained in step (6) on the above mother powder, and then cover it with the mother powder of the same composition. Finally, invert the crucible on the alumina crucible cover and gently press the crucible and crucible cover to ensure sealing. Immediately put the sealed crucible into the muffle furnace and heat it to 1000℃ at a rate of 4℃ / min, then heat it to 1200℃ at a rate of 3℃ / min, and then keep it at this temperature for 12h. After cooling, open the crucible cover and take out the dense crystalline ceramic material. Example 7
[0032] (1) Na 3.18 Zr 1.82 Tb 0.18 Si2PO 12 Treatment of raw material powders: Sodium carbonate (Na2CO3) was calcined at 900°C for 6 hours to promote its decomposition and purification, zirconium oxide (ZrO2) was calcined at 900°C for 8 hours to remove adsorbed moisture and possible organic matter, and silicon dioxide (SiO2), ammonium hydrogen phosphate (NH4H2PO4) and terbium oxide (Tb2O3) were dried at 120°C for 24 hours; (2) Weighing and mixing: Synthesize 12 g Na 3.18 Zr 1.82 Tb 0.18 Si2PO 12 The stoichiometric weighing step (1) of Na, Zr, Tb, Si and P requires 3.7233 g (Na2CO3 99%), 4.9542 g (ZrO2 99%), 2.6559 g (SiO2 99%), 2.5399 g (NH4H2PO4 99%) and 0.4114 g (Tb2O3 99%) of raw material powders, wherein 15 wt% excess Na2CO3 and NH4H2PO4 are weighed to compensate for the volatilization loss of sodium at high temperature; (3) Grinding and mixing: In a dust-free environment, place the weighed raw material powder in a clean agate mortar, add anhydrous ethanol as a grinding aid, and ball-mill at a rate of 1200 r / min for 0.5 h. Grind and mix evenly, and evenly load the ball-milled mixture into a crucible, and ensure that the crucible lid is sealed to prevent volatilization and oxidation; (4) Powder synthesis: Place the crucible loaded with raw materials steadily into a preheated muffle furnace, heat it to 950°C at a rate of 3°C / min, and keep it in this temperature range for 6 hours. Allow the crucible to cool naturally to about 200°C along with the furnace temperature. After taking out the synthesized powder, grind it in a mortar for 60 minutes to improve its fineness and uniformity to obtain the final powder; (5) Granulation and tableting: Weigh 0.8 g of the precursor powder obtained in step (4) above, add 5% by weight of polyvinyl butyral (PVB) solution to the powder to enhance the adhesion of the powder. The amount of PVB solution added is 20% of the mass of the precursor powder. Grind in an agate mortar to mix the powder and PVB solution evenly. After it is completely dried, place the powder in a mold and keep it under a pressure of 30 MPa for 1 min for granulation. Keep the granulated powder under a pressure of 50 MPa for 1 min to obtain a solid electrolyte formed sheet with a diameter of 10 mm and a thickness of 1.8 mm; (6) Debinding: Place the molded sheet pressed in step (5) in an oven at 50°C to remove the anhydrous ethanol in the adhesive. After preheating, take out the molded sheet and cool it to room temperature, then place it upright in an open crucible in a muffle furnace, heat it to 500°C at a rate of 1°C / min, and keep it at 500°C for 2 hours to perform debinding treatment to ensure complete volatilization of organic matter. After debinding is completed, turn off the heating and let the molded sheet cool naturally to room temperature along with the temperature in the furnace to obtain a sample sheet; (7) Sintering: Before sintering, use the mother powder of the same composition to spread about 1mm thick on the inside of the alumina crucible, and use a tool to gently compact the mother powder. Place the sample sheet obtained in step (6) on the above mother powder, and then cover it with the mother powder of the same composition. Finally, invert the crucible on the alumina crucible cover and gently press the crucible and crucible cover to ensure sealing. Immediately put the sealed crucible into the muffle furnace and heat it to 900℃ at a rate of 3℃ / min, then heat it to 1200℃ at a rate of 5℃ / min, and then keep it at this temperature for 12h. After cooling, open the crucible cover and take out the dense crystalline ceramic material.
[0033] Comparative Example 1
[0034] (1) Na3Zr2Si2PO 12 Treatment of raw material powders: Sodium carbonate (Na2CO3) is calcined at 900℃ for 3 hours to promote its decomposition and purification, zirconium oxide (ZrO2) is calcined at 900℃ for 6 hours to remove adsorbed moisture and possible organic matter, and silicon dioxide (SiO2) and ammonium hydrogen phosphate (NH4H2PO4) are dried at 120℃ for 12 hours to remove moisture from the raw materials; (2) Weighing and mixing: Synthesize 5g Na3Zr2Si2PO 12 According to the stoichiometric ratio of Na, Zr, Tb, Si and P, the raw material powders required in step (1) are (Na2CO399%) 1.4889 g, (ZrO299%) 2.3080 g, (SiO299%) 1.1255 g, and (NH4H2PO499%) 1.0587 g, wherein 15 wt% excess Na2CO3 and NH4H2PO4 are weighed to compensate for the volatilization loss of sodium at high temperature; (3) Grinding and mixing: In a dust-free environment, place the weighed raw material powder in a clean agate mortar, add anhydrous ethanol as a grinding aid, and ball mill at a rate of 1200r / min for 0.5 hours to grind and mix evenly. Load the ball-milled mixture evenly into the crucible and ensure that the crucible lid is sealed to prevent volatilization and oxidation; (4) Powder synthesis: Place the crucible loaded with raw materials steadily into a preheated muffle furnace, heat it to 900°C at a rate of 5°C / min, and keep it in this temperature range for 6 hours. Allow the crucible to cool naturally to about 200°C along with the furnace temperature. After taking out the synthesized powder, grind it in a mortar for 30 minutes to improve its fineness and uniformity to obtain the final powder; (5) Granulation and tableting: Weigh 0.7 g of the precursor powder obtained in step (4) above, add a 5% mass concentration of polyvinyl butyral (PVB) solution to the powder to enhance the adhesion of the powder. The amount of PVB solution added is 20% of the mass of the precursor powder. Grind in an agate mortar to mix the powder and PVB solution evenly. After it is completely dried, place the powder in a mold and keep it under a pressure of 30 MPa for 1 min for granulation. Keep the granulated powder under a pressure of 50 MPa for 1 min to obtain a solid electrolyte formed sheet with a diameter of 10 mm and a thickness of 1.5 mm; (6) Debinding: Place the molded sheet pressed in step (5) in an oven at 50°C to remove the anhydrous ethanol in the adhesive. After preheating, take out the molded sheet and cool it to room temperature, then place it upright in an open crucible in a muffle furnace, heat it to 500°C at a rate of 1°C / min, and keep it at 500°C for 2 hours to perform debinding treatment to ensure complete volatilization of organic matter. After debinding is completed, turn off the heating and let the molded sheet cool naturally to room temperature along with the temperature in the furnace to obtain a sample sheet; (7) Sintering: Before sintering, use the mother powder of the same composition to spread about 1mm thick on the inside of the alumina crucible, and use a tool to gently compact the mother powder. Place the sample sheet obtained in step (6) on the above mother powder, and then cover it with the mother powder of the same composition. Finally, turn the crucible upside down on the alumina crucible lid and gently press the crucible and crucible lid to ensure sealing. Immediately put the sealed crucible into the muffle furnace and heat it to 900℃ at a rate of 5℃ / min, then heat it to 1100℃ at a rate of 3℃ / min, and then keep it at this temperature for 6h. After cooling, open the crucible lid and take out the ceramic material.
[0035] Comparative Example 2
[0036] (1) Na 3.4 Zr 1.6 Tb 0.4 Si2PO 12Treatment of raw material powders: Sodium carbonate (Na2CO3) is roasted at 900℃ for 9 hours to promote its decomposition and purification, zirconium oxide (ZrO2) is roasted at 900℃ for 12 hours to remove adsorbed moisture and possible organic matter, and silicon dioxide (SiO2) and ammonium hydrogen phosphate (NH4H2PO4) are dried at 120℃ for 24 hours; (2) Weighing and mixing: Synthesize 9g Na 3.4 Zr 1.6 Tb 0.4 Si2PO 12 The stoichiometric weighing step (1) of Na, Zr, Tb, Si and P requires 2.8325 g (Na2CO3 99%), 3.0990 g (ZrO2 99%), 1.8891 g (SiO2 99%), 1.8072 g (NH4H2PO4 99%) and 0.6505 g (Tb2O3 99%) of raw material powders, wherein 15 wt% excess Na2CO3 and NH4H2PO4 are weighed to compensate for the volatilization loss of sodium at high temperature; (3) Grinding and mixing: In a dust-free environment, place the weighed raw material powder in a clean agate mortar, add anhydrous ethanol as a grinding aid, and ball mill at a rate of 1200r / min for 1 hour to grind and mix evenly. Load the ball-milled mixture evenly into the crucible and ensure that the crucible lid is sealed to prevent volatilization and oxidation; (4) Powder synthesis: Place the crucible loaded with raw materials steadily into a preheated muffle furnace, heat it to 900°C at a rate of 4°C / min, and keep it in this temperature range for 6 hours. Allow the crucible to cool naturally to about 200°C along with the furnace temperature. After taking out the synthesized powder, grind it in a mortar for 30 minutes to improve its fineness and uniformity to obtain the final powder; (5) Granulation and tableting: Weigh 0.8 g of the precursor powder obtained in step (4) above, add a 5% mass concentration of polyvinyl butyral (PVB) solution to the powder to enhance the adhesion of the powder. The amount of PVB solution added is 20% of the mass of the precursor powder. Grind in an agate mortar to mix the powder and the PVB solution evenly. After it is completely dried, place the powder in a mold and keep it under a pressure of 30 MPa for 1 min for granulation. Keep the granulated powder under a pressure of 50 MPa for 1 min to obtain a solid electrolyte formed sheet with a diameter of 10 mm and a thickness of 1.8 mm; (6) Debinding: Place the molded sheet pressed in step (5) in an oven at 50°C to remove the anhydrous ethanol in the binder. After preheating, take out the molded sheet and cool it to room temperature. Then, place it upright in an open crucible in a muffle furnace and heat it to 500°C at a rate of 1°C / min. Keep it at 500°C for 2 hours to perform debinding treatment to ensure complete volatilization of organic matter. After debinding is completed, turn off the heating and let the molded sheet cool naturally to room temperature along with the temperature in the furnace to obtain a sample sheet.
[0037] (7) Sintering: Before sintering, use the mother powder of the same composition to spread about 1mm thick on the inside of the alumina crucible, and use a tool to gently compact the mother powder. Place the sample sheet obtained in step (6) on the above mother powder, and then cover it with the mother powder of the same composition. Finally, invert the crucible on the alumina crucible cover and gently press the crucible and crucible cover to ensure sealing. Immediately put the sealed crucible into the muffle furnace and heat it to 1000℃ at a rate of 4℃ / min, then heat it to 1200℃ at a rate of 3℃ / min, and then keep it at this temperature for 12h. After cooling, open the crucible cover and take out the dense crystalline ceramic material.
[0038] Comparative Example 3
[0039] (1) Na 3.2 Zr 1.8 Tb 0.2 Si2PO 12 Treatment of raw material powders: Sodium carbonate (Na2CO3) is roasted at 900℃ for 9 hours to promote its decomposition and purification, zirconium oxide (ZrO2) is roasted at 900℃ for 12 hours to remove adsorbed moisture and possible organic matter, and silicon dioxide (SiO2) and ammonium hydrogen phosphate (NH4H2PO4) are dried at 120℃ for 24 hours; (2) Weighing and mixing: Synthesize 12 g Na 3.2 Zr 1.8 Tb 0.2 Si2PO 12 The stoichiometric weighing step (1) of Na, Zr, Tb, Si and P requires 3.6723 g (Na2CO3 99%), 4.80214 g (ZrO2 99%), 2.6020 g (SiO2 99%), 2.6841 g (NH4H2PO4 99%) and 1.1689 g (TbCl3 99%) of raw material powders, wherein 15 wt% excess Na2CO3 and NH4H2PO4 are weighed to compensate for the volatilization loss of sodium at high temperature; (3) Grinding and mixing: In a dust-free environment, place the weighed raw material powder in a clean agate mortar, add anhydrous ethanol as a grinding aid, and ball-mill at a rate of 1200 r / min for 0.5 h. Grind and mix evenly, and evenly load the ball-milled mixture into a crucible, and ensure that the crucible lid is sealed to prevent volatilization and oxidation; (4) Granulation and tableting: Weigh 0.8 g of the precursor powder obtained in step (3) above, add 5% polyvinyl butyral (PVB) solution to the powder to enhance the adhesion of the powder. The amount of PVB solution added is 20% of the mass of the precursor powder. Grind in an agate mortar to mix the powder and PVB solution evenly. After it is completely dried, place the powder in a mold and keep it under a pressure of 30 MPa for 1 min for granulation. Keep the granulated powder under a pressure of 50 MPa for 1 min to obtain a solid electrolyte formed sheet with a diameter of 10 mm and a thickness of 1.8 mm; (5) Debinding: Place the molded sheet pressed in step (4) in an oven at 50°C to remove the anhydrous ethanol in the binder. After preheating, take out the molded sheet and cool it to room temperature, then place it upright in an open crucible in a muffle furnace, heat it to 500°C at a rate of 1°C / min, and keep it at 500°C for 2 hours to perform debinding treatment to ensure complete volatilization of organic matter. After debinding is completed, turn off the heating and let the molded sheet cool naturally to room temperature along with the temperature in the furnace to obtain a sample sheet.
[0040] (6) Sintering: Before sintering, use the mother powder of the same composition to spread about 1mm thick on the inside of the alumina crucible, and use a tool to gently compact the mother powder. Place the sample sheet obtained in step (5) on the above mother powder, and then cover it with the mother powder of the same composition. Finally, invert the crucible on the alumina crucible cover and gently press the crucible and crucible cover to ensure sealing. Immediately put the sealed crucible into the muffle furnace and heat it to 1000℃ at a rate of 5℃ / min, then heat it to 1200℃ at a rate of 2℃ / min, and then keep it at this temperature for 9h. After cooling, open the crucible cover and take out the dense crystalline ceramic material.
[0041] The ceramic samples synthesized in Examples 1 to 3 and the Na3Zr2Si2PO4 synthesized in Comparative Example 1 were 12 The ceramic samples were subjected to X-ray diffraction analysis, and the results were as follows: Figure 1 As shown. For the terbium-doped ceramic sample Na 3+x Zr 2-x Tb x Si2PO 12 , the monoclinic phase is (PDF # 35-0412), and the rhombohedral phase is (PDF # 33-1313). Among them, when Tb (x=0.1, 0.2, 0.3) is added, the sintered ceramic sample compound shows a gradual transition from the monoclinic phase to the rhombohedral phase.
[0042] As the concentration of terbium (Tb) doping increases from 0 to 0.3 mol, NASICON will gradually transition from the monoclinic phase to the rhombohedral phase. No impurities are generated during the entire doping process, indicating that the doping element Tb has good compatibility with the host material and no side reactions occur. Observing the doping phase of the NASICON sample, this transition can be observed by the change in the relative peak intensity at 19.2° and 19.6°. For the rhombohedral phase, the peak intensity at 19.2° is greater than the peak intensity at 19.6° (e.g. Figure 1 ). With the increase of Tb content, the transition from monoclinic phase to rhombohedral phase is promoted. 12 The ionic conductivity of solid electrolyte is high (up to 1.02×10 -3 S cm -1 , see Table 1), and the grains in its microstructure are smaller.
[0043] For the sample Na synthesized in Example 2 3.2 Zr 1.8 Tb 0.2 Si2PO 12 Scanning electron microscope test, its microstructure is as follows Figure 2 As shown. Figure 2 It can be seen that with the increase of Tb 3+ With the entry of doping, the size of the grains gradually decreases, and the fusion and connection between the grains are enhanced, resulting in a denser structure and lower porosity.
[0044] Determination of Na synthesized in Examples 1-3 and Comparative Example 1 3+x Zr 2-x Tb x Si2PO 12 The AC impedance curve of the system sample is as follows: Figure 3 As shown, it provides information about the impedance variation of the system at different frequencies.
[0045] The ionic conductivity was determined using the calculation formula σ = L / RS, where L represents the thickness of the sample and S represents the area of the electrode. The room temperature conductivity of the ceramic material samples of each composition is shown in Tables 1 and 2.
[0046] Table 1 Na 3+x Zr 2-x Tb x Si2PO 12 (0<x≤0.3) Conductivity of the system at 30℃
[0047] Table 2 Na 3+x Zr 2-x Tb xSi2PO 12 (x=0, 0.2, 0.4) conductivity of the system at 30℃
[0048] As shown in Tables 1 and 2, the conductivity of the terbium-doped NASICON solid electrolyte increases with the increase of the appropriate amount of doping. 3.2 Zr 1.8 Tb 0.2 Si2PO 12 The total conductivity of the sample at room temperature (30°C) is 1.02×10 -3 S cm -1 , the sample grains are small, and the high-density grain boundaries in the fine-grained NASICON ceramics can disperse the current more effectively, thereby delaying the formation of dendrites and improving the cycle performance of the sodium ion battery. And the sintering temperature of the present invention is low, which reduces energy consumption. However, the undoped terbium comparative example 1 and the excessively doped terbium comparative example 2 exhibit low ionic conductivity, because the excessive doped terbium ions may produce too many defects in the lattice, thereby hindering the migration of ions, and for comparative example 3, the ionic conductivity is poor after using TbCl3 instead of Tb2O3. The reason may be that chloride doping may cause changes in the lattice parameters, which may affect the crystal structure and ion transport channels of the material, thereby affecting the mobility and conductivity of the ions.
[0049] Figure 4 and Figure 5 The polarization current-time curves of the electrolyte when an external voltage of 1 V is applied for different time periods are depicted. 3+ Compared with the undoped NASICON electrolyte, it can be observed that the steady-state current rise rate of the doped electrolyte is significantly slowed down. This phenomenon reveals that the doped Tb 3+ It can improve the ion conductivity of the electrolyte and slow down the growth rate of the current, thereby allowing more ions to pass through in a steady state. This property has a positive effect on inhibiting the formation of sodium dendrites and helps to improve the safety and stability of the battery.
Claims
1. A terbium-doped NASICON type sodium ion conductor material, characterized in that: The stoichiometric formula of the terbium-doped NASICON type sodium ion conductor material is Na 3+x Zr 2-x Tb x Si2PO 12 , where 0<x≤0.
3.
2. The terbium-doped NASICON type sodium ion conductor material according to claim 1, characterized in that: The total ionic conductivity of the terbium-doped NASICON sodium ion conductor material is 3.07×10 -4 S / cm~1.02×10 -3 S / cm.
3. A method for preparing the terbium-doped NASICON type sodium ion conductor material as claimed in claim 1 or 2, characterized in that: The preparation steps include the following: 1) Processing of raw material powders: calcining Na2CO3 powder and ZrO2 powder at high temperature, and drying SiO2 powder, NH4H2PO4 powder and Tb2O3 powder; 2) Weighing and batching: Based on Na 3+x Zr 2-x Tb x Si2PO 12 Weigh the Na2CO3, ZrO2, SiO2, NH4H2PO4 and Tb2O3 raw material powders processed in step 1) according to the stoichiometric ratio of Na, Zr, Tb, Si and P, wherein excess Na2CO3 and NH4H2PO4 are weighed to compensate for the volatilization loss of sodium at high temperature; 3) Grinding and mixing: In a dust-free environment, ball-mill the weighed raw material powder and grinding aid to mix them evenly; evenly load the ball-milled mixed powder into the crucible and ensure that the crucible cover is sealed; 4) Powder synthesis: Place the crucible loaded with the mixed powder in step 3) into a preheated muffle furnace, heat it to 900-1000°C at a rate of 3-5°C / min, and maintain it in this temperature range for 6-12 hours, let the crucible cool naturally to 180-220°C with the furnace temperature, take out the synthesized powder, and grind it in a mortar to obtain the final precursor powder; 5) Granulation and tableting: weigh the precursor powder obtained in step 4) above, add polyvinyl butyral solution to the precursor powder, grind in an agate mortar to mix the powder and polyvinyl alcohol solution evenly, and after completely drying, put the powder into a mold for granulation, and keep the granulated powder under pressure to obtain a solid electrolyte formed sheet; 6) Debinding: Place the solid electrolyte formed sheet pressed in step 5) in an oven, preheat, take out the solid electrolyte formed sheet and cool it to room temperature, then place it upright in an open crucible in a muffle furnace for debinding. After debinding, turn off the heating and allow the solid electrolyte formed sheet to cool naturally to room temperature along with the temperature in the furnace to obtain a sample sheet; 7) Sintering: Before sintering, use the mother powder of the same composition to spread on the inner side of the alumina crucible, compact the mother powder to ensure that it is evenly distributed on the surface of the crucible cover, place the sample sheet obtained in step 6) on the mother powder, and then cover it with the mother powder of the same composition. Finally, turn the crucible upside down on the alumina crucible cover and gently press the crucible and the crucible cover to ensure the sealing. Immediately put the sealed crucible into a muffle furnace and heat it to 900-1000°C at a heating rate of 5°C / min, then heat it to 1100-1200°C at a rate of 3°C / min, and then keep it at this temperature for 6-12h. After cooling, open the crucible cover and take out the dense crystalline ceramic material.
4. The method according to claim 3, characterized in that: In step 1), the high temperature calcination conditions of Na2CO3 powder are: calcination temperature 900°C, calcination time 5 to 9 hours; the high temperature calcination conditions of ZrO2 powder are: calcination temperature 900°C, calcination time 8 to 12 hours; the drying conditions of SiO2, NH4H2PO4 and Tb2O3 are: drying at 120°C for 12 to 24 hours.
5. The method according to claim 3, characterized in that: In step 3), the grinding aid is anhydrous ethanol, and the ball milling conditions are: ball milling at a rate of 1200 r / min for 0.5 to 1 hour.
6. The method according to claim 3, characterized in that: In step 5), the amount of the polyvinyl alcohol solution added is 20% of the precursor powder, and the mass concentration of the polyvinyl alcohol solution is 5%.
7. The method according to claim 3, characterized in that: In step 6), the method of debinding treatment is: firstly heating to 500°C at 1°C / min, and keeping at 500°C for 2 hours for debinding treatment.
Citation Information
Patent Citations
Ferro-aluminum co-doped garnet-type Li7La3Zr2O12 lithium-ion conductor material and preparing method thereof
CN109626996A
Nasicon type sodium-ion solid electrolyte, preparation method and application thereof
CN109786815A
Sodium ion solid electrolyte with NASICON structure as well as preparation method and application of sodium ion solid electrolyte
CN115832415A
Preparation method of Na3Zr2Si2PO12 solid electrolyte
CN116799292A
Cited By
Rb-doped NASICON type solid sodium-ion battery electrolyte material as well as preparation method and application of Rb-doped NASICON type solid sodium-ion battery electrolyte material
CN122338188A
Rb-doped NASICON-type solid-state sodium-ion battery electrolyte material, preparation method and application thereof
CN122338188B